Effective action for QED in 2+1 dimensions at finite temperature - Hott, Marcelo [UNESP]; Metikas, Georgios (American Physical Society (APS), 1999)
Both the parity-breaking and parity-invariant parts of the effective action for the gauge field in QED 3 with massive fermions at finite temperature are obtained exactly. This is feasible because we use a particular configuration of the background gauge field, namely a constant magnetic field and a time-dependent time component of the background gauge field. Our results allow us to compute exactly physically interesting quantities such as the induced charge density and fermion condensate whose dependence on the temperature, fermion mass and gauge field is discussed. ©1999 The American Physical Society.